KAMPANYE "INGAT PESAN IBU: 3M" TERHADAP KEPATUHAN MENJALANI PROTOKOL KESEHATAN COVID-19 - Dharmayani, Made Ayu Sunilaningrat; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2023)
“Adaptasi Kebiasaan Baru (AKB)” or new normal era is a preventive policy released by government in order to save the national economy which is getting weaker due to the pandemic and to save the increasing number of confirmed positive Covid-19 patients. Therefore the government become more vigorous in carrying out health protocols, one of it is through the “Ingat Pesan Ibu: 3M” campaign on television. Through this research, esearcher want to find out the impact of “Ingat Pesan Ibu: 3M” campaign on compliance with the Covid-19 health protocol. This research used a method named qualitative with case study approach. U nit of analysis focuse d on people. N on-probability sampling technique also used to determine the informants . The results showed the “Ingat Pesan Ibu: 3M” campaign on television had an impact in the form of community compliance in carrying out the 3M movements (wearing masks, washing hands and maintaining distance).